Combating School Bullying through Developmental Guidance for Positive Youth Development and Promoting Harmonious School Culture - Eadaoin K. P. Hui; Sandra K. M. Tsang; Bella C. M. Law (The Scientific World Journal)
Bullying and violence, which can bring detrimental effects, are situations which young people have to face in their process of development. Though school bullying has been a spreading and explicit problem in Hong Kong schools, most of the programs or guidelines dealing with the problem lack citywide, recognized initiatives and the effectiveness of these programs is unknown due to the lack of evaluation. The present paper discusses preventing school bullying from a developmental guidance perspective, using the positive youth development paradigm and promoting the values of harmony and forgiveness at the whole-school level to cultivate a harmonious school culture as a way of combating school bullying.